PENGARUH PENGGUNAAN MODEL PEMBELAJARAN CONCEPT SENTENCE TERHADAP HASIL BELAJAR BIOLOGI SISWA PADA MATERI EKOSISTEM DI KELAS X TAMAN MADYA (SMA) TAMANSISWA PEMATANGSIANTAR - Tridelpina Purba, Sumarny; Perayanti Sinaga, Dian; Saragih, Putri Minati (Jurnal Metabio, 2023)
This study aimed to determine the effect of the concept sentence learning model on biology learning outcomes in ecosystems for tenth-grade students of Taman Madya (SMA) Tamansiswa Pematangsiantar. The population of this study was 191 students, consisting of five classes. Sampling was conducted using cluster random sampling, resulting in two classes: class X IPA 1 (38 students) and class X IPA 2 (38 students), resulting in a total sample of 76 students. Data analysis was performed using normality tests, homogeneity tests, and hypothesis testing (t-tests) at a significance level of α = 0.05. The results showed that the average post-test score for the experimental class was 88.68, while the average post-test score for the control class was 85.13. From the results of the hypothesis testing, it was obtained that t_(Count) (2.338) > t_(table) (1.992), so Ho was rejected and Ha was accepted, meaning that there was an influence of the use of the Concept Sentence learning model on Biology learning outcomes in ecosystem material in class X Taman Madya (SMA) Tamansiswa Pematangsiantar